George William Burton papers - Burton, George William, 1858-1941.
Correspondence with William Howard Taft, programs, invitations, souvenirs, and other memorabilia, relating to Wisconsin and national politics, Robert M. La Follette, Taft's visits to Wisconsin, and other matters. Some of the letters are from Wendell W. Mischler, Taft's secretary.
Banker, of LaCrosse, Wis.
Collection material in English.
Keywords: Mischler, Wendell W., -- 1870- -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; La Follette, Robert M. -- 1855-1925.; Wisconsin -- Politics and government; United States -- Politics and government -- 1909-1913.; Bankers